THE EFFECT OF COPAL RESIN AND TURPENTINE OIL AS TACKIFIER ON THE ADHESIVES QUALITY BASED OF LIQUID RUBBER COMPOUND - Widayanti, Tri; Sutanto, Teja Dwi; Gustian, Irfan (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2024)
This research aims to develop adhesives from liquid rubber compounds with a variety of tackifiers, a combination of copal resin, and turpentine oil. It also aims to characterize the adhesives to determine the quality of the adhesives produced. The research comprised several stages, including the preparation of rubber additive dispersions and solutions, formulation of liquid rubber compounds and adhesives, fabrication of test pieces, and subsequent characterization. The liquid rubber compound is made by mixing concentrated latex with rubber additives, which include KOH as a stabilizer, stearic acid and ZnO as an activator, BHT as an antioxidant, CaCO3 as a filler, MBTS and TMTD as an accelerator, and sulfur as a vulcanizer. The adhesives are made by mixing liquid rubber compound with tackifier material with various combinations of copal resin/turpentine oil, namely F1 (0 gram/4 gram); F2 (1 gram/3 grams); F3 (2 grams/2 grams), F4 (3 grams/1 gram), and F5 (4 grams/0 grams). Adhesives characterization was carried out by testing pH, viscosity, adhesives strength, FTIR, XRD, and thermal analysis. The research results showed that the best conditions were obtained on F4 adhesives with an adhesives strength value of 1.7452 N/mm, viscosity of 1100 cP, and pH 4.6. In this condition, the resulting adhesives meet the requirements for adhesives in accordance with SNI 06-6049-1999 and SNI 12-7195-2006.